Variation of Heating Rate in Determining Melting Temperature Using Differential Scanning Calorimetry - Warmiati Warmiati; Wijayanti Wijayanti (Politeknik ATK Yogyakarta, 2025)
An experimental study on the variation of heating rates in determining melting temperature using Differential Scanning Calorimetry (DSC) was conducted. This research aimed to investigate the effect of different heating rates on the determination of melting temperature using DSC, employing Indium Standard Reference Material (SRM) Lot BD147. The standard and sample were analyzed at heating rates of 5, 10, 15, 20, and 25°C/min. The resulted melting temperatures were analyzed using ANOVA, which revealed statistically significant differences. Heating rates of 5, 15, 20, and 25°C/min showed significant deviations from the standard rate of 10°C/min, indicating that 10°C/min is the most suitable rate for accurate melting temperature analysis based on ISO 11357-3.